THE ROLE OF TURNOVER, WORK ROTATION AND EFFECTIVENESS IN EMPLOYEE PRODUCTIVITY: PERAN TURNOVER, ROTASI KERJA DAN EFEKTIVITAS TERHADAP PRODUKTIVITAS KARYAWAN - Arta Rusidarma Putra; Silfiana Silfiana (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
This research aims to determine and examine the effect of turnover, job rotation and effectiveness on employee productivity. The population and sample are 48 employees. The data collection method used was questionnaires and the analytical techniques used were multiple linear regression, F test, t test and determination test. The results showed: 1) Turnover has a positive and significant effect on productivity. 2) Job rotation has a positive and significant effect on productivity. 3) Effectiveness has no positive and insignificant effects on productivity. 4) Turnover, job rotation and effectiveness simultaneously have positive and significant effects on productivity